Analisis Ketaatan Pengendalian Pencemaran Air oleh Fasilitas Kesehatan di Surabaya Melalui Pelaporan E-Simpel DLH Kota Surabaya - Wahyu Salsa Fajar Apria; Nurvita Cundaningsih (Faculty of Engineering, Universitas Serambi Mekkah, 2025)
Water pollution from waste, particularly from the healthcare sector, is a serious problem in urban areas such as Surabaya. Liquid waste that is not properly managed can pollute the environment and threaten public health. To address this problem, the city government of Surabaya has implemented an electronic reporting system (E-Simpel). This study aims to determine the level of compliance, especially by health facilities, in reporting environmental management efforts, one of which is water pollution control. The method used is a descriptive quantitative analysis to see the compliance of the implementation of liquid waste management in health facilities in Surabaya with the applicable laws and regulations. The focus of the research is on the compliance of health facilities in reporting waste quality data through the E-Simple system. The results of the study show that there is a difference in the average score of water pollution control compliance of health facilities in Surabaya, with the average score of air pollution control compliance being higher in 2024 than in 2023.